Neonatal Mortality: Review from a Tertiary Hospital in Rawalpindi - Rubina Zulfqar, Samiya Naeemullah (Journal of Rawalpindi Medical College, 2009)
Background: A prospective study was conducted in the neonatal intensive care unit of department of Paediatrics, Holy Family Hospital, Rawalpindi, from 1st January, 2006 to 30th June, 2006. Methods: All neonates admitted were enrolled in this study. Sixteen hundred thirty one neonates were admitted. Results: The major cases admitted were 617 (37.82%) cases of neonatal sepsis, followed by prematurity 333 (20.41%), birth asphyxia, 299 (18.33%), neonatal jaundice 146 (8.95%) and 75 (4.59%) cases of meconium aspiration. The number of neonates who expired were 383 (23.48%), while 1190(72.96%), were discharged and 58(3.55%) left against medical advice. Among the neonates expired there were 236 (61.6%) males and 147 (38.4%) females. SVD was the predominant mode of delivery in 303 (79.0%) and LSCS in 80 (20.9%). Babies delivered at HFH were 156 (40.7%) with 102 (26.6%) home delivered, 79 (20.6%) from private hospitals while 46 (12%) were from Children Hospital and other government hospitals of Rawalpindi/Islamabad. Most neonates presented before 24 hrs of age 230 (60.1%), whereas 63 (16.4%) presented between 24 – 72 hrs and 90 (23.5%) presented between 72 hrs and 28 days. Most expiries occurred in less than 24 hrs after admission 167 (43.6%), followed by expiries in > than72 hrs and between 24 – 72 hrs of stay, 113 (29.6%) and 103 (26.8%) respectively. The major contributors to mortality were birth asphyxia 13 (43.8%), pre maturity 129 (38.7%), meconium aspiration 13 (7.3%), neonatal sepsis 75 (12.15%) and neo natal jaundice 1 (10.27%) Conclusion: Age of presentation is an important contributor to neonatal mortality. The importance of focusing on facility based clinical care, with involvement of out reach teams, family and community cannot be over emphasized ..